SOME HINTS ON OPEN READING FRAME STATISTICS — HOW ORF LENGTH DEPENDS ON SELECTION - GIERLIK, AGNIESZKA; MACKIEWICZ, PAWEŁ; KOWALCZUK, MARIA; CEBRAT, STANISŁAW; DUDEK, MIROSŁAW R. (International journal of modern physics. C, Computational physics, physical computation, 1999)
Coding sequences of DNA generate Open Reading Frames (ORFs) inside them with much higher frequency than random DNA sequences do, especially in the antisense strand. This is a specific feature of the genetic code. Since coding sequences are selected for their length, the generated ORFs are indirect results of this selection and their length is also influenced by selection. That is why ORFs found in any genome, even much longer ones than those spontaneously generated in random DNA sequences, should be considered as two different sets of ORFs: The first one coding for proteins, the second one generated by the coding ORFs. Even intergenic sequences possess greater capacity for generating ORFs than random DNA sequences of the same nucleotide composition, which seems to be a premise that intergenic sequences were generated from coding sequences by recombinational mechanisms.